Electrospun nanofibers of polymer nanocomposite with cichorium intybus extract and investigating their antioxidant and antibacterial activities - Mohamed, Ahmed Emadelddin (AUC Knowledge Fountain, 2019)
Micro-organisms causing diseases have been quickly increasing and spreading vastly in their ability to gain resistance against current antibiotics in the market. This results in an enormous mortality rate. Fortunately, Scientists introduced nanotechnology that can further enhance properties of materials in the nanoscale. This allowed further openings to upgrade natural-based products to become more effective and safer than current synthetic antibiotics. In this study, biodegradable polymer nanocomposite made up of Poly Vinyl alcohol (PVA) with Chitosan (CS) was electro-spun using the electro-spinner embedded with Chicory root herbal extract that can potentially be used for targeting Gastro Intestinal Tract (GIT) diseases. This study is divided into 3 phases. Phase I included refining and optimising the extract using 2 different solvents (Distilled Water and Ethanol 70%) and 2 drying methods (Sun and Freeze Drying). Phase II optimised the parameters of the electro-spinner to produce smooth PVA/CS Nanofibers (NFs) using the Scanning Electron Microscope (SEM). Phase III optimised the concentration of PVA/CS/Ex. NFs using the Fourier Transform-Infra Red spectroscopy, Ultra Violet-Visible Light spectrophotometer to indicate the Total Phenolic Contents, Entrapment Efficiency (EE), Loading Capacity (LC), release kinetics, antioxidant activity and antibacterial activity. Results of phase I have shown, that the freeze dried ethanolic extract had the highest yield % at 24.7% with total phenolic contents (TPCs) of 4mg Gallic Acid Equivalent (GAE)/1g, 80% antioxidant activity at 25 mg with an IC50 of 4.15 mg/ml as well as an Minimum Bactericidal Concentration (MBC) of 100 mg with Staphylococcus Aureus and 25 mg with Escherichia Coli. While results of phase III indicated that PVA/CS/Ex 0.5% NFs was the optimum system, which had an IC50 of 33.32 mg/mL, EE 64.89%, LC of 4.41% obeying Korsmeyer Peppas release model for 48 h showing Quasi Fickian behaviour. PVA/CS/Ex 0.5% NFs had an MBC of 2 mg in both strains, Staphylococcus Aureus and Escherichia coli proving to be a potent antibacterial material compared to Vancomycin and Ceftriaxone with a balanced antioxidant activity.